Physical training as the basis of professional activities of patrol policemen - KOSTIANTYN PRONTENKO; VALENTIN BONDARENKO; SERGIY BEZPALIY; DMYTRO KYSLENKO; YURII LISNICHENKO; VASYL OLLO; ALLA ALOSHYNA; OLEXANDR BYCHUK; VOLODYMYR SMIRNOV (Baltic Journal of Health and Physical Activity, 2020)
Background: ‪Physical training is an integral part of policemen’s professional training. The aim of the study is to verify experimentally the effectiveness of the authors’ methodology of training future patrol policemen targeted at increasing their general physical fitness level during the primary professional training course. Material and methods: T‪he study involved the patrol policemen of the primary professional training course (N = 115) of the National Academy of Internal Affairs. The level of physical fitness was assessed by the following tests: 100-m race, pull-ups, push-ups, 1000-m race, shuttle run 4 х 9 m, sit-ups, standing long jump, sitting forward bend, and the plank. Results: ‪The obtained data show that the level of general physical fitness of experimental groups’ policemen is significantly better (p < 0.05–0.001) than in control groups’ policemen at the end of the experiment in terms of the level of power, endurance, flexibility, speed and static endurance. Conclusions: ‪The excellent physical fitness level, which was formed during the primary professional training course, will contribute to maintaining a proper level of physical condition and health of policemen and their professional longevity, as well as improving their professional performance.